Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.3346/jkms.2001.16.5.573
|View full text |Cite
|
Sign up to set email alerts
|

Focal Organizing Pneumonia: CT and Pathologic Findings

Abstract: The purpose of this study was to describe the CT findings of focal organizing pneumonia and to compare the findings with pathology. CT findings of histologically proven focal organizing pneumonias in 26 consecutive patients were analyzed. In 17 patients who had undergone surgical resections, the findings were correlated with pathology. Focal organizing pneumonias appeared as a nodule (n= 13) or a mass (n=13), ranging from 9 mm to 66 mm in diameter. Ground-glass opacity was seen in 6/13 (46%) nodules and 6.5/13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 18 publications
(24 reference statements)
2
21
0
1
Order By: Relevance
“…Some cases overlap with other types of idiopathic interstitial pneumonias (IPF), especially IPF and nonspecific interstitial pneumonia (NSIP). In the latter, focal areas of organizing pneumonia are often encountered at histopathology (18). The radiographic findings of the present case showed solitary focal opacity and the patient had no respiratory symptoms.…”
Section: Discussionsupporting
confidence: 43%
“…Some cases overlap with other types of idiopathic interstitial pneumonias (IPF), especially IPF and nonspecific interstitial pneumonia (NSIP). In the latter, focal areas of organizing pneumonia are often encountered at histopathology (18). The radiographic findings of the present case showed solitary focal opacity and the patient had no respiratory symptoms.…”
Section: Discussionsupporting
confidence: 43%
“…The lesions are often located in the upper lobes, and may be cavitary. The clinical presentation may be that of COP as described above, but focal organising pneumonia may be totally asymptomatic and discovered by routine chest radiographs (some patients may recall that they had a previous history of pneumonia) [17,90,145]. The suspicion of carcinoma may be increased by false-positive fluorodeoxyglucose positron emission uptake [147,148].…”
Section: Solitary Focal Opacitymentioning
confidence: 99%
“…However, organising pneumonia is distinct from round pneumonia improving with antibiotics [142][143][144]. Neutrophilic inflammation or microabscesses may be associated with the typical features of organising pneumonia [145,146]. The lesions are often located in the upper lobes, and may be cavitary.…”
Section: Solitary Focal Opacitymentioning
confidence: 99%
“…In addition, it has been reported that 69%-94% of the nodules of organizing pneumonia had irregular margins, suggesting lower compactness. 16,22 The mean compactness of organizing pneumonia, adenocarcinoma, and squamous cell carcinomas was low, and a signifi cant difference was not noted among these three diseases. Metastasis showed the second largest value after hamartoma.…”
Section: Discussionmentioning
confidence: 93%